C.F. Gauss and the method of least squares - Sheynin, Oscar (Silesian Statistical Reviev, 2014)
Gauss introduced the MLSq and Helmert completed its development whereas Bessel made important discoveries in astronomy and geodesy but was often extremely inattentive. Gauss’ final condition of least variance led to effective estimators of the unknowns sought, jointly effective in case of the normal distribution of the observational errors. Gauss’ memoire of 1823 leads to the principle of least squares much easier than generally thought
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2014, nr 12 (18), s. 9-37
Keywords: principle and method of least squares; sample variance; adjustment of triangulation; personal equation; deviation from normality